A Comprehensive Study on Optimal Energy Efficient Routing Protocols for Life Time Conservation of Wireless Sensor Networks - Prabakaran, K.; Suresh, G.; Kumaratharan, N.; Senthil Kumar, N.C. (International Journal of Psychosocial Rehabilitation, 2020)
In General, energy efficient routing protocols in WSN are the precise domain which enables the designer to deploy variety of protocols. WSNs are an integration of multi functional nodes which are tiny, low powered and smaller in size. Moreover, energy efficiency among sensor nodes is one of the important issues that need to be solved in WSN for attaining good quality of service. Hence, it is vital to save sensor node energy while meeting the requirements of the user either by changing energy source or can be recharged. The life time of WSN can be increased based on optimal routing protocols that accentuate data dissemination and bandwidth constraints. WSN has design techniques or routing protocols that contribute the trade-off between energy, latency, security, data aggregation, stability factors and other metrics for the focus of QoS. This paper presents an extensive survey of state-of-the-art of the modern routing protocols to facilitate robustness. Further, in this paper the performance metrics, main advantages and disadvantages of each routing algorithm are compared and scope of future enhancement is discussed.